Regeneration method of waste lithium iron phosphate battery material
Through disassembly, water vapor pressurized peeling, crushing, mixing and calcining, the regeneration problem of the positive electrode active substance of lithium iron phosphate battery is solved, and the ideal electrochemical performance and consistency of the material is achieved.
Patent Information
- Application Number
- CN202510371503.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-27
AI Technical Summary
在磷酸铁锂电池的回收过程中,如何使得正极活性物质获得理想的电化学性能。
By disassembly and separate the positive electrode sheet, the residual electrolyte is removed, the positive electrode active material layer and current collector are peeled off by water vapor pressurization reaction, and then pulverizing, mixing, spray granulation and calcining treatment are carried out to control the heating rate to form a uniform lithium iron phosphate material.
The full regeneration of lithium iron phosphate positive electrode material has been achieved, and ideal electrochemical properties and consistent material quality have been achieved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery material regeneration, and more specifically, relates to a method for regenerating materials of waste lithium iron phosphate batteries. Background Art
[0002] During the processing, testing and use of lithium-ion batteries, a large amount of battery waste is generated, among which the recycling of battery positive electrode materials is particularly valuable. For batteries with lithium iron phosphate as the positive electrode material, since the lithium iron phosphate positive electrode material is an olivine structure, its physical structure is stable. However, in actual use, it needs to be carbon-coated or doped, and these coatings or dopants may be destroyed during processing, testing or use. Therefore, it still needs to be regenerated after recycling in order to obtain ideal electrochemical properties of the lithium iron phosphate positive electrode material. Summary of the invention
[0003] The technical problem to be solved by the present invention is: for lithium iron phosphate batteries, how to make the product obtain ideal electrochemical properties during the recovery and regeneration of its positive electrode active material. The present invention provides a method for regenerating materials of waste lithium iron phosphate batteries.
[0004] The purpose of the present invention is to provide a method for regenerating materials of waste lithium iron phosphate batteries.
[0005] The above-mentioned purpose of the present invention is achieved through the following technical solutions: A method for regenerating materials of waste lithium iron phosphate batteries, the specific regeneration steps comprising: Disassembling and separating to obtain the positive electrode sheet, and then drying to remove the residual electrolyte solvent in the positive electrode sheet, so that the fluorine-containing lithium salt in the electrolyte is adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The positive electrode sheet is laid in the reactor, preheated to 100°C, and water vapor is introduced into the reactor. After the pressure is maintained at 0.3-0.5MPa for 1-3h, the pressure is released to normal pressure, the material is discharged, the positive electrode current collector is separated and removed, and the positive electrode active material layer is collected; crushing the positive electrode active material layer to obtain positive electrode active material layer crushed material; According to weight proportions, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, heated to 300-310°C in an inert atmosphere, kept for melting reaction for 4-8 hours, cooled, washed with water, dried, heated to 660-680°C in an inert atmosphere, kept for calcination for 4-8 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
[0006] Beneficial effects of the above technical solution: First, the recovered positive electrode sheet is dried. During this process, the electrolyte absorbed in the pores of the positive electrode sheet will begin to evaporate. At this time, the solvent in the electrolyte mainly evaporates, while the fluorine-containing lithium salt in the electrolyte remains in the pores of the positive electrode sheet. Subsequently, water vapor is used for pressurization reaction, and water vapor will continuously diffuse and penetrate into the pores of the positive electrode sheet. In this process, the fluorine-containing lithium salt remaining in the pores can react with water vapor to produce HF. It should be noted that due to the temperature and pressure in the reactor, HF and water vapor diffuse and penetrate into the pores of the positive electrode sheet under the vapor pressure, so that the bonding interface between the positive electrode active material layer on the surface of the positive electrode sheet and the positive electrode current collector (aluminum foil) is effectively and fully destroyed. In the process of decompression to normal pressure, due to the rapid reduction of pressure, the internal HF and water vapor are quickly released. In this process, it can further facilitate the peeling of the interface between the positive electrode active material layer and the positive electrode current collector. In the subsequent regeneration process, the existence of pores formed by the diffusion and penetration of water vapor and HF gas will facilitate the diffusion and penetration of molten material into the internal pores, thereby achieving sufficient and uniform replenishment of lithium, iron and other elements for the positive electrode active material; so that the electrochemical performance of the regenerated lithium iron phosphate positive electrode material can achieve ideal results.
[0007] Furthermore, the specific regeneration step also includes: The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed, stirred to form a slurry, and then the obtained slurry is sprayed and granulated to obtain active material particles; Take 100-110 parts of active material particles, 15-20 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar by weight, mix them evenly, heat them to 300-310°C in an inert atmosphere, keep them melted for 4-8 hours, cool them, wash them with water, dry them, heat them to 660-680°C in an inert atmosphere, keep them calcined for 4-8 hours, cool them, and discharge them, thus completing the regeneration of the materials of the waste lithium iron phosphate battery.
[0008] Furthermore, the specific regeneration step also includes: The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed and stirred to form a slurry, and the obtained slurry is sprayed and granulated, and active material particles with a D50 of 80-120 μm are sieved.
[0009] In the above technical solution, the positive electrode active material layer fragments and N-methylpyrrolidone are further mixed. In this process, N-methylpyrrolidone can redissolve the binder (PVDF) in the positive electrode active material layer fragments to form a slurry, and in the spray drying process, with the help of the binding effect of PVDF, the positive electrode active material is formed into spherical particles, which is beneficial to increase the contact area with the molten salt in the subsequent regeneration process. In addition, during the spray granulation process, the diffusion of the solvent N-methylpyrrolidone forms pores, which not only reduces the density of the active material particles, making it easy to suspend them in the molten salt system to avoid sedimentation, but also provides a diffusion path for the molten salt, so that the molten salt treatment process is sufficient and uniform.
[0010] Furthermore, the biomass sugar is selected from any one of glucose, fructose, galactose, lactose and sucrose.
[0011] Furthermore, the specific preparation steps also include: According to weight proportion, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, and then slowly heated to 300-310°C at a rate of 0.3-0.5°C / min in an inert atmosphere, and melt-reacted for 4-8 hours, cooled, washed with water, and dried, and then heated to 660-680°C in an inert atmosphere, and calcined for 4-8 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
[0012] Furthermore, the specific preparation steps also include: According to weight proportion, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, slowly heated to 300-310°C at a rate of 0.3-0.5°C / min in an inert atmosphere, kept for melting reaction for 4-8h, cooled, washed with water, dried, and then quickly heated to 660-680°C at a rate of 3-5°C / min in an inert atmosphere, kept for calcination for 4-8h, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
[0013] The above technical solution further controls the heating rate during the melting process, and adopts a lower heating rate for slow heating, so that the melting process of the molten salt is controlled. This is mainly because the thermal conductivity of the molten salt is different from the thermal conductivity between the positive electrode active material particles. During the melting process, the heat transfer needs to rely on the internal heat transfer between the two. The slow heating rate can make the overall temperature of the system relatively balanced, avoiding local overheating, which leads to uneven reaction and inconsistent final processed product areas, which is undesirable.
[0014] Furthermore, the fluorine-containing lithium salt is selected from any one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalatoborate.
[0015] Furthermore, the mass of the fluorine-containing lithium salt accounts for 5-12% of the total mass of the electrolyte. DETAILED DESCRIPTION
[0016] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0017] Unless otherwise specified, the reagents and materials used in the following examples are commercially available. Example 1
[0018] A square aluminum shell battery with lithium iron phosphate as the main positive electrode material is used as the recycling object, and the battery is obtained by disassembling the battery pack; The battery is fully discharged to a cut-off voltage of 2.5V, which is considered to be in an empty state to ensure safety during disassembly and recycling; The positive electrode sheet is disassembled and separated. At this time, the positive electrode sheet is still infiltrated with electrolyte. In this state, it is then dried in an oven at 80° C. to constant weight to remove the residual electrolyte solvent in the positive electrode sheet. Since the electrolyte includes a solvent and a fluorine-containing lithium salt dissolved therein, after evaporating and removing the solvent, the fluorine-containing lithium salt in the electrolyte can be adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The fluorine-containing lithium salt is selected from lithium hexafluorophosphate; The mass of the fluorine-containing lithium salt accounts for 5% of the total mass of the electrolyte; The positive electrode sheet is laid in the reactor, and a hydrothermal reactor is used as the reactor. After preheating it to 100°C, superheated water vapor is introduced into the reactor. After maintaining the pressure for 1 hour at a pressure of 0.3MPa, the pressure is released to normal pressure and the material is discharged. At this time, the positive electrode active material layer on the surface of the positive electrode sheet has been peeled off from the positive electrode collector. The positive electrode collector is separated and removed, and the positive electrode active material layer is collected; crushing the positive electrode active material layer to obtain positive electrode active material layer crushed material; The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed in a mass ratio of 1:8, stirred to form a slurry, and then the obtained slurry is pumped into a spray dryer for spray granulation, and active material particles with a D50 of 80 μm are screened out; Take 100 parts of active material particles, 20 parts of lithium nitrate, 3 parts of ferrous oxalate, and 5 parts of biomass sugar by weight, mix them evenly, and slowly heat them to 300°C at a rate of 0.3°C / min in an inert atmosphere, keep them melted for 4 hours, cool them, wash them with water, dry them, and quickly heat them to 660°C at a rate of 3°C / min in an inert atmosphere, keep them calcined for 4 hours, cool them, and discharge them, thus completing the regeneration of the materials of the waste lithium iron phosphate battery; The biomass sugar is selected from glucose. Example 2
[0019] A square aluminum shell battery with lithium iron phosphate as the main positive electrode material is used as the recycling object, and the battery is obtained by disassembling the battery pack; The battery is fully discharged to a cut-off voltage of 2.5V, which is considered to be in an empty state to ensure safety during disassembly and recycling; The positive electrode sheet is disassembled and separated. At this time, the positive electrode sheet is still infiltrated with electrolyte. In this state, it is then dried in an oven at 80° C. to constant weight to remove the residual electrolyte solvent in the positive electrode sheet. Since the electrolyte includes a solvent and a fluorine-containing lithium salt dissolved therein, after evaporating and removing the solvent, the fluorine-containing lithium salt in the electrolyte can be adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The fluorine-containing lithium salt is selected from lithium tetrafluoroborate; The mass of the fluorine-containing lithium salt accounts for 8% of the total mass of the electrolyte; The positive electrode sheet is laid in the reactor, and a hydrothermal reactor is used as the reactor. After preheating it to 100°C, superheated water vapor is introduced into the reactor. After maintaining the pressure for 2 hours at a pressure of 0.4MPa, the pressure is released to normal pressure and the material is discharged. At this time, the positive electrode active material layer on the surface of the positive electrode sheet has been peeled off from the positive electrode collector. The positive electrode collector is separated and removed, and the positive electrode active material layer is collected; crushing the positive electrode active material layer to obtain positive electrode active material layer crushed material; The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed in a mass ratio of 1:8, stirred to form a slurry, and then the obtained slurry is pumped into a spray dryer for spray granulation, and active material particles with a D50 of 100 μm are screened out; According to the weight percentage, 105 parts of active material particles, 22 parts of lithium nitrate, 4 parts of ferrous oxalate, and 6 parts of biomass sugar are taken, mixed evenly, and then slowly heated to 305°C at a rate of 0.4°C / min in an inert atmosphere, kept for melting reaction for 6 hours, cooled, washed with water, and dried, and then quickly heated to 670°C at a rate of 4°C / min in an inert atmosphere, kept for calcination for 6 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials; The biomass sugar is selected from sucrose. Example 3
[0020] A square aluminum shell battery with lithium iron phosphate as the main positive electrode material is used as the recycling object, and the battery is obtained by disassembling the battery pack; The battery is fully discharged to a cut-off voltage of 2.5V, which is considered to be in an empty state to ensure safety during disassembly and recycling; The positive electrode sheet is disassembled and separated. At this time, the positive electrode sheet is still infiltrated with electrolyte. In this state, it is then dried in an oven at 80° C. to constant weight to remove the residual electrolyte solvent in the positive electrode sheet. Since the electrolyte includes a solvent and a fluorine-containing lithium salt dissolved therein, after evaporating and removing the solvent, the fluorine-containing lithium salt in the electrolyte can be adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The fluorine-containing lithium salt is selected from any one of lithium difluorooxalate borate; The mass of the fluorine-containing lithium salt accounts for 12% of the total mass of the electrolyte; The positive electrode sheet is laid in the reactor, and a hydrothermal reactor is used as the reactor. After preheating it to 100°C, superheated water vapor is introduced into the reactor. After maintaining the pressure for 3 hours at a pressure of 0.5MPa, the pressure is released to normal pressure and the material is discharged. At this time, the positive electrode active material layer on the surface of the positive electrode sheet has been peeled off from the positive electrode collector. The positive electrode collector is separated and removed, and the positive electrode active material layer is collected; crushing the positive electrode active material layer to obtain positive electrode active material layer crushed material; The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed in a mass ratio of 1:8, stirred to form a slurry, and then the obtained slurry is pumped into a spray dryer for spray granulation, and active material particles with a D50 of 120 μm are screened out; According to the weight percentage, 110 parts of active material particles, 25 parts of lithium nitrate, 5 parts of ferrous oxalate, and 8 parts of biomass sugar are taken, mixed evenly, and then slowly heated to 310°C at a rate of 0.5°C / min in an inert atmosphere, kept for melting reaction for 8 hours, cooled, washed with water, and dried, and then quickly heated to 680°C at a rate of 5°C / min in an inert atmosphere, kept for calcination for 8 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials; The biomass sugar is selected from fructose. Example 4
[0021] Compared with Example 1, the present embodiment differs in that the positive electrode active material layer crushed material is directly subjected to the subsequent regeneration process without spray granulation. Specifically: The positive electrode active material layer is crushed, and particles with a D50 of 80 μm are sieved to obtain positive electrode active material layer crushed material; According to the weight percentage, take 100 parts of positive electrode active material layer fragments, 20 parts of lithium nitrate, 3 parts of ferrous oxalate, and 5 parts of biomass sugar, mix them evenly, and then slowly heat them to 300°C at a rate of 0.3°C / min in an inert atmosphere. After keeping the melting reaction for 4 hours, cool, wash, and dry them. Then, in an inert atmosphere, quickly heat them to 660°C at a rate of 3°C / min, keep them warm and calcine for 4 hours, cool, and discharge the materials. The regeneration of the waste lithium iron phosphate battery materials is completed. Example 5
[0022] Compared with Example 1, the difference between this embodiment is that the heating rate during the melting process is 3°C / min, and the other conditions remain unchanged, specifically: Take 100 parts of active material particles, 20 parts of lithium nitrate, 3 parts of ferrous oxalate, and 5 parts of biomass sugar by weight, mix them evenly, and then heat them to 300°C at a rate of 3°C / min in an inert atmosphere. After keeping the melt reaction for 4 hours, cool, wash, and dry them. Then, heat them to 660°C at a rate of 3°C / min in an inert atmosphere. After keeping the calcination for 4 hours, cool and discharge the materials. The regeneration of waste lithium iron phosphate battery materials is completed.
[0023] Comparative Example 1 Compared with Example 1, this comparative example has the following differences: A square aluminum shell battery with lithium iron phosphate as the main positive electrode material is used as the recycling object, and the battery is obtained by disassembling the battery pack; The battery is fully discharged to a cut-off voltage of 2.5V, which is considered to be in an empty state to ensure safety during disassembly and recycling; The positive electrode sheet is disassembled and separated. At this time, the positive electrode sheet is still infiltrated with electrolyte. In this state, it is then dried in an oven at 80° C. to constant weight to remove the residual electrolyte solvent in the positive electrode sheet. Since the electrolyte includes a solvent and a fluorine-containing lithium salt dissolved therein, after evaporating and removing the solvent, the fluorine-containing lithium salt in the electrolyte can be adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The fluorine-containing lithium salt is selected from lithium hexafluorophosphate; The mass of the fluorine-containing lithium salt accounts for 5% of the total mass of the electrolyte; The positive electrode sheet is laid in the reactor, and a hydrothermal reactor is used as the reactor. After preheating it to 100°C, deionized water is added to the reactor, and after heating to 100°C, the reactor is kept warm and immersed for 1 hour, and the material is discharged and filtered. At this time, the positive electrode active material layer on the surface of the positive electrode sheet has been peeled off from the positive electrode collector, and the positive electrode collector is separated and removed to collect the positive electrode active material layer; The positive electrode active material layer is crushed to obtain positive electrode active material layer crushed materials.
[0024] The performance tests were performed on the products obtained in the embodiments and comparative examples. The specific test methods and test results are as follows: Weigh according to the mass ratio m (regenerated lithium iron phosphate material): m (acetylene black): m (PVDF) = 8:1:1. Place the lithium iron phosphate material and acetylene black in a blast drying oven and dry at 100°C for 2 hours. At the same time, dissolve PVDF in N-methylpyrrolidone and stir magnetically for 2 hours until it is evenly mixed. Grind and sieve the dried lithium iron phosphate material and acetylene black in a mortar, add them to the above-mentioned PVDF N-methylpyrrolidone solution, and stir until a uniform black slurry is formed. Apply the slurry on aluminum foil with a coating thickness of 80μm, then transfer it to a blast drying oven, take it out after drying at 90°C for 2 hours, then roll it with a pressure of 1.8MPa, and finally slice it using a button battery punching machine to obtain a positive electrode sheet.
[0025] The battery was assembled in a vacuum glove box filled with Ar. The assembled battery model was CR2016. The positive sheet obtained above was used as the positive electrode, the lithium sheet was used as the counter electrode, and 1 mol / L LiPF6 / EC.DMC.EMC was used as the electrolyte. The positive electrode shell, positive electrode sheet, diaphragm (Celgard 2400), lithium sheet, gasket, spring sheet, and negative electrode shell were placed in sequence, and a button battery was made using a sheet pressing machine. The battery was aged in the glove box for 12 hours and then taken out for testing. The lithium iron phosphate material prepared in the same embodiment or comparative example was used to prepare three groups of batteries according to the above-mentioned battery preparation method, so as to evaluate the performance consistency of the materials obtained in the same batch of embodiments or comparative examples; The LAND CT2001A battery testing system was used to test the cycle performance of the button battery. The test environment temperature was 25°C and the voltage window was 2.5-4.2V. During the charging process, the charging rate in the constant current stage was 0.3C. After the constant voltage stage, it was terminated at 0.05C and considered fully charged. The discharge rate was 0.1C and discharged to the cut-off voltage. The nominal specific capacity of LFP was set to 170mAh / g. The capacity retention rate after 100 cycles under the corresponding rate conditions was tested to evaluate its cycle performance.
[0026] The detailed test results are shown in Table 1: Table 1: Product performance test results
[0027]
[0028] It can be seen from the test results in Table 1 that, since Example 4 did not perform spray granulation, the consistency of the product during the regeneration process was affected, and the test results between different groups had the largest deviation. In Comparative Example 1, the pretreatment in the early stage was insufficient due to the lack of water vapor pressurization. Compared with Example 1, the uniformity and product capacity retention rate were relatively poor.
[0029] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for regenerating materials from waste lithium iron phosphate batteries, characterized in that: The specific regeneration steps include: Disassembling and separating to obtain the positive electrode sheet, and then drying to remove the residual electrolyte solvent in the positive electrode sheet, so that the fluorine-containing lithium salt in the electrolyte is adsorbed in the pores of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is lithium iron phosphate; The positive electrode sheet is laid in the reactor, preheated to 100°C, and water vapor is introduced into the reactor. After the pressure is maintained at 0.3-0.5MPa for 1-3h, the pressure is released to normal pressure, the material is discharged, the positive electrode current collector is separated and removed, and the positive electrode active material layer is collected; crushing the positive electrode active material layer to obtain positive electrode active material layer crushed material; According to weight proportions, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, heated to 300-310°C in an inert atmosphere, kept for melting reaction for 4-8 hours, cooled, washed with water, dried, heated to 660-680°C in an inert atmosphere, kept for calcination for 4-8 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
2. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The specific regeneration step also includes: The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed, stirred to form a slurry, and then the obtained slurry is sprayed and granulated to obtain active material particles; Take 100-110 parts of active material particles, 15-20 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar by weight, mix them evenly, heat them to 300-310°C in an inert atmosphere, keep them melted for 4-8 hours, cool them, wash them with water, dry them, heat them to 660-680°C in an inert atmosphere, keep them calcined for 4-8 hours, cool them, and discharge them, thus completing the regeneration of the materials of the waste lithium iron phosphate battery.
3. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 2, characterized in that: The specific regeneration step also includes: The positive electrode active material layer crushed material and solvent N-methylpyrrolidone are mixed and stirred to form a slurry, and the obtained slurry is sprayed and granulated, and active material particles with a D50 of 80-120 μm are sieved.
4. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The biomass sugar is selected from any one of glucose, fructose, galactose, lactose and sucrose.
5. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The specific preparation steps also include: According to weight proportion, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, and then slowly heated to 300-310°C at a rate of 0.3-0.5°C / min in an inert atmosphere, and melt-reacted for 4-8 hours, cooled, washed with water, and dried, and then heated to 660-680°C in an inert atmosphere, and calcined for 4-8 hours, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
6. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 5, characterized in that: The specific preparation steps also include: According to weight proportion, 100-110 parts of positive electrode active material layer crushed material, 20-25 parts of lithium nitrate, 3-5 parts of ferrous oxalate, and 5-8 parts of biomass sugar are taken, mixed evenly, slowly heated to 300-310°C at a rate of 0.3-0.5°C / min in an inert atmosphere, kept for melting reaction for 4-8h, cooled, washed with water, dried, and then quickly heated to 660-680°C at a rate of 3-5°C / min in an inert atmosphere, kept for calcination for 4-8h, cooled, and discharged, thereby completing the regeneration of waste lithium iron phosphate battery materials.
7. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The fluorine-containing lithium salt is selected from any one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalatoborate.
8. The method for regenerating materials of waste lithium iron phosphate batteries according to claim 7, characterized in that: The mass of the fluorine-containing lithium salt accounts for 5-12% of the total mass of the electrolyte.
Citation Information
Patent Citations
Direct regeneration method of waste nickel-based positive electrode material
CN116387669A
Recycling process of waste ternary battery positive electrode material
CN117790963A
Dry-type physical recovery method of lithium iron phosphate battery positive plate leftover material
CN117800303A
Cited By
Method and system for recycling pole piece of waste power battery
CN120940361A